Post-structuralist geography a guide to relational space - Murdoch, Jonathan 1954-2005 (SAGE, 2006)
An introduction to post-structuralist theory that critically assesses how the concept can be used to study space and place this text communicates a new agenda for the study of human geography
Neue Seitenzählung in jedem Kapitel, abweichend von Seitenzählung in print-Version
Literaturangaben und Index
Keywords: Geography -- Philosophy; Poststructuralism; Geografie; Poststrukturalismus; Strukturforschung; Anthropogeografie; Raumordnung; Bildungspolitik; Großbritannien; Aufsatzsammlung